3D Printed Metamaterial Capacitive Sensing Array for Universal Jamming Gripper and Human Joint Wearables. Issue 5 (24th May 2021) - Loh, Leon Yeong Wei; Gupta, Ujjaval; Wang, Yingxi; Foo, Choon Chiang; Zhu, Jian; Lu, Wen Feng
Abstract : The metamaterial sensor array has the ability to conform to a spherical surface as shown. The slight separation between the array and the sphere implies that the array is not only limited to a spherical surface but can conform to other curved surfaces. A blown‐up view shows capacitive sensor electrodes being embedded within the metamaterial sensor array. Further details can be found in the article, number 2001082, by Jian Zhu, Wen Feng Lu, and co‐workers.